Convex Bodies with Identical John and LYZ Ellipsoids. (19th December 2016) - Zou, Du; Xiong, Ge
Abstract: Convex bodies with identical John and LYZ ellipsoids are characterized. This solves an important problem from convex geometry posed by G. Zhang. As applications, several sharp affine isoperimetric inequalities are established.